Advanced PLC control and computer simulation of a new generation woodworking machinery. - Topraç, Deniz (My University, 1999)
Günümüzde mobilya üretim tesislerinde genellikle standart mobilya üretimi yapılmaktadır. Yüksek kapasiteli bu üretim sistemleri esneklikten uzak olup az miktarda özellikli ürün siparişlerini kısa zamanda ve ekonomik olarak karşılayamamaktadırlar. Müşteri talepleri giderek daha özelleşmekte, kalite beklentisi artmakta ve teslim tarihi beklentisi daha da kısalmaktadır. EUREKA evesinde geliştirilen St.Joseph 2000 projesi, İtalyan, Fransız, İspanyol ve Türk firma ve araştırma kurumlarının biraraya gelmesi ile oluşturulmuş; yeni nesil ağaç işleme makinalarının esnek ve tam zamanlı üretim yapan entegre üretim tesislerinde kullanılabilmesi için hızlı otomasyon ve yapay görme sistemleri ile desteklenmesini ele alan bir projedir. Bu proje kapsamında SCM Italy ( Ağaç işleme makinaları üreticisi ) tarafından yeni nesil ağaç işleme makinaları tasarlanmakta ve geliştirilmektedir. Bu makinalar tek olarak çalışabilecekleri gibi modüler yapıya sahip olup bloklar halinde birleştirilebilirler. Makinaların önemli bir özelliği de elektronik teknolojisindeki gelişmeleri takip edebilecek şekilde tasarlanmalarıdır. Bu tezde , yeni tasarlanan bu makinaların özellikleri incelenmekte ve İtalyan üreticiler ile birlikte tasarlanan makine kontrol yazılımı tanıtılmaktadır. INTRODUCTION Nowadays, there is a strong trend in the furniture industry towards customization. More than 70% of furniture production in Europe is carried out by Small and Medium Enterprises (SME). For SME's, as well as for large manufacturers, the satisfaction of customer's needs producing Just in Time customized furniture at low cost is crucial to stay in business. The state of the art systems are not able to adequately satisfy the above specified requirements; in fact, they have been designed for mass production of standard furniture. These systems are highly productive but the degree of flexibility is very low and not acceptable for the new needs of the market. The production of great batches from one side causes optimization in the use of rough materials and high productivity, from the other side, causes high costs in management of great buffers, passive operations of stocking materials and picking of it which do not add value to the product. The aim of the Eureka St.Joseph 2000 project is to study, develop and realize a system integrating new woodworking machinery with open architecture advanced distributed information system and machine vision. The ability to adapt to possible future technological developments will be a major factor in the design of the machines to be developed in the project. From the other side the proposed project aims to integrate fast ethernet technology in the industrial world for building generic computing environment ( hardware and software) to be applied to advanced manufacturing process control and supervision combining high data flows, high performance, real time control of an agile just in time (JIT) production system. The thesis aims to study the new woodworking machinery components, its functions, control software and its integration to the information network.
Keywords: Makineler; Uygulamalı fizik